Short course treatment of pulmonary tuberculosis patients suffering from multiple drug resistance. The current situation and future perspectives - A. E. Russkikh; D. M. Kutuzova; O. V. Lovacheva; A. G. Samoylova; I. A. Vasilyeva (Туберкулез и болезни лёгких)
The article presents a review of 70 publications. It describes relevant data on drugs, timing, indications, efficacy, and safety of short-term treatment regimens for multiple drug resistant tuberculosis.